Food-borne disease prevalence in rural villages in the Eastern Cape, South Africa - Khanya Z. Bisholo; Shanaz Ghuman; Firoza Haffejee (AOSIS, 2018)
Background: The highest burden of food-borne diseases is in Africa. Despite this, food safety does not seem to be a major concern in many African countries. There is also a lack of concern within rural areas of South Africa. Aim: The aim of this study was to determine the prevalence of food-borne diseases in rural areas in the Eastern Cape, South Africa, by comparing data obtained from a cross-sectional survey and clinic records. Setting: The study was conducted in Ncera, Mpongo and Needscamp villages in the Eastern Cape, South Africa. Methods: In the first phase of the study, a random sample of household heads (n = 87) were interviewed to determine the prevalence of food-borne diseases between 2012 and 2014. In the second phase, registers from clinics serving the villages were screened for food-borne disease cases during the same time period. Results: A total of 109 (27.3%) household members fell ill because of food-borne diseases. Half (n = 56; 51.3%) of the respondents who fell ill because of food-borne diseases did not seek medical treatment for their illness. Of those who sought treatment, 19 (46%) attended primary health care clinics. However, examination of the clinic registers showed only four recorded cases of food-borne diseases. Conclusion: The prevalence of food-borne diseases in rural villages in the Eastern Cape, South Africa, was reported as high but the records in clinic registers are low, indicating a gap in the health care system. Monitoring of these diseases needs to improve.